Anxiety, family support, and sleep quality in patients with congestive heart failure - Istiqomah, Nina; Rahayu, Tutik; Weriningsih, Apriliani Yulianti (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Sleep disturbances are common in patients with congestive heart failure (CHF), which can negatively impact quality of life and worsen clinical symptoms. Purpose: To examine the influence of anxiety and family support on sleep quality among patients. Method: The research methodology for this study was a cross-sectional descriptive analytical design. Through the use of a purposive sampling approach, 75 participants were selected for this study. The research instruments used in this study were the HPSS, the MOS Social Support Survey, and the Pittsburgh Sleep Quality Index (PSQI). Results: Patients with CHF had a statistically significant correlation between their anxiety levels and their sleep quality (p = 0.032). Patients' sleep quality was negatively affected by their anxiety levels. There was no statistically significant correlation between family support and sleep quality (p = 0.457). Conclusion: In patients with CHF, anxiety levels were significantly correlated with poor sleep quality, although family support was not. Keywords: Anxiety; Congestive Heart Failure; Family Support; Sleep Quality.